Optimizing the sequential approach of combined phacoemulsification and gonioscopy-assisted transluminal trabeculotomy (GATT) in primary open-angle glaucoma - Shaoyang Zhang; WenJing He; Peng Lu; Fan Xu; Haibin Zhong; Shan Zhong; Li Jiang (BMC Ophthalmology)
Abstract Background To evaluate the efficacy, safety and complication of different procedure sequence combining gonioscopy-assisted transluminal trabeculotomy (GATT) either before or after phacoemulsification for patient with primary open-angle glaucoma (POAG) and cataract. Method This retrospective, clinic control study included 82 patients (82 eyes) with a diagnosis of POAG with cataract. The patients were divided into two groups: Phaco-GATT group underwent phacoemulsification followed by GATT and GATT-Phaco group underwent GATT followed by phacoemulsification. Intraocular pressure (IOP) changes, best-corrected visual acuity (BCVA), visual field Mean Deviation (MD) and antiglaucoma medication (AGM) were analyzed preoperatively and at postoperatively 1d, 1w, 1 m, 3 m, 6 m, and 12 m. Postoperative complications, including hyphema, IOP spikes, and suprachoroidal effusion, were closely reported. Result A total of 40 eyes were subjected to Phaco-GATT group, and 42 eyes were subjected to GATT-Phaco group. For all patients, significant IOP and AGM reduction and BCVA improvement were observed at each follow-up time points compare to preoperation (all P > 0.05). At 12 months, the visual field MD in the GATT-Phaco group was significantly improved than that in the Phaco-GATT group (P < 0.05). GATT-Phaco group appeared to have less AGM than those in Phaco-GATT group from postoperative 1 month to 12 months, though there was no significantly difference (all P > 0.05). At 12 months postoperatively, GATT-Phaco group demonstrated a slightly higher complete success rate of 76.2% and qualified success rates of 90.5% compare to Phaco-GATT (65.0% and 85.0%). Moreover, in the GATT-Phaco group, BCVA was significantly improved and macrohyphema (> 1 mm) was reduced compare to Phaco-GATT group at early stage. Additionally, no statistically significant differences were observed in IOP spike, descemet’s membrane detachment, and supraciliary effusion between two groups at each time point. Conclusion This study demonstrates that combined phacoemulsification and GATT is a safe and effective treatment for POAG patients with cataract. Both surgical sequences are effective, however, initiating with GATT may provide more benefits compare phacoemulsification prior.